PATHOGENIC MECHANISMS OF PRIMARY HEADACHE IN CHILDREN - L.A. Pak; I.E. Smirnov; V.M. Studenikin; A.V. Goriunova; O.I. Maslova ("Paediatrician" Publishers LLC, 2006)
The article reflects current viewpoints of Russian and foreign scientists on a problem of pathology of primary headaches (migraine and tension headache) in children, it's frequency in adults and children, diagnostic aspects and characteristic features of clinical course in children. Much attention is paid to the role of nitric oxide in pathogenesis of primary headaches.Key words: headache, primary headache, tension headache, migraine, nitric oxide, children.